The PNPT project - Urso, A. (EWF Scientific Magazine, 2020)
PNPT® is an acronym for Psycho-Neuro Programming for Training, the study of a subjective experience (individual therefore and unrepeatable) of how each individual (each single person) perceives, lives, realizes and transforms the entire training process, as well as its phases, into the acquisition of skills. It is presented as a model of organization, communication, evalua-tion and continuous reprogramming, which allows us to analyse almost every behaviour and every autonomous choice, every adaptation made, breaking them down into sequences of observable, reproducible, modifiable, and within certain limits, measurable elements. Here are the basic contents of the acronym PNPT®. • Psycho: the approach to training is not only methodological. The method is to be considered something that must be adapted day by day to the psychical, behavioural and personality structure conditions of each individual athlete. Person and personality before the method. But not just one method, but many changing methods: its intrinsic variability belongs to the method. • Neuro: every motor adaptation must be considered as the result of particular and complex neurological processes; the evaluation of these processes, which are therefore training processes, require constant evaluation and remodulation, in order to carefully and appropriately manage the individual response to the stress represented by the workload. • Programming: the manifested behaviours and the organic responses of each individual are the consequence of specific "programming for training" in which the data collected must be analysed and are always functional to the continuous reorganization of the stimulus administration process. • Training: the final process of the programmatic organization, where the correct stimuli to be administered find space and acquire relevance to create new and sustainable stress processes and, at the same time, to remodel the stressogenic stimuli that have already exhausted their possible physiological and adaptive response content.